The Importance of Implementing a Transition Strategy for Patients with Muscular Dystrophy: From Child to Adult-Insights from a Tertiary Centre for Rare Neurological Diseases - Maria Lupu; Mihaela Ioghen; Radu-Ștefan Perjoc; Andra-Maria Scarlat; Oana Aurelia Vladâcenco; Eugenia Roza; Diana Ana-Maria Epure; Raluca Ioana Teleanu; Emilia Maria Severin (MDPI AG, 2023)
Progress in the field of muscular dystrophy (MD) using a multidisciplinary approach based on international standards of care has led to a significant increase in the life expectancy of patients. The challenge of transitioning from pediatric to adult healthcare has been acknowledged for over a decade, yet it continues to be a last-minute concern. Currently, there is no established consensus on how to evaluate the effectiveness of the transition process. Our study aimed to identify how well patients are prepared for the transition and to determine their needs. We conducted a descriptive, cross-sectional study on 15 patients aged 14 to 21 years. The patients completed a sociodemographic and a Transition Readiness Assessment Questionnaire (TRAQ). We also analyzed the comorbidities of these patients. Our study revealed that only 46.7% of the patients had engaged in a conversation with a medical professional, namely, a child neurologist, about transitioning. A total of 60% of the participants expressed having confidence in their self-care ability. However, the median TRAQ score of 3.6 shows that these patients overestimate themselves. We emphasize the necessity for a slow, personalized transition led by a multidisciplinary team to ensure the continuity of state-of-the-art care from pediatric to adult healthcare services and the achievement of the highest possible quality of life for these patients.